A study on cultural adaptation of Chinese Students in Indonesia - Yan, Yinyan (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
As closer cooperation in education between Guangxi and Indonesia, the cross-cultural adaptation of foreign students in target countries has become a very important issue. In terms of society, psychology, learning and culture, the article studies the adaptation of international students who come from Guangxi University of Foreign Language in Indonesia by means of questionnaires and interviews. Their cultural adaptation is generally good, but there are many differences in gender, length of study abroad, cultural experience, etc..This thesis will analyze the factors that affect cross-cultural adaptation and the reasons for the differences, and provide relevant suggestions for further improving at training program.